2011
DOI: 10.1037/a0024525
|View full text |Cite
|
Sign up to set email alerts
|

The case for treating depression in military spouses.

Abstract: The increased operational tempo associated with current deployments to Operation Iraqi Freedom (OIF) and Operation Enduring Freedom (OEF) is placing considerable strain on military families. Among other sequelae of OIF and OEF deployment, findings from recent studies suggest high rates of depression in spouses of service members. This review presents a rationale for targeting depression among military spouses. It examines how stressors relating to the deployment cycle may contribute to depression in spouses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 76 publications
1
47
0
Order By: Relevance
“…Inconsolable crying, bed-wetting, aggression and temper tantrums were observed. This early finding that the non-deployed parent's mental health predicted children's depression, internalising and externalising symptoms, mirrors consistent findings in contemporary military family research (Drummet, Coleman, & Cable, 2003;Flake, Davis, Johnson, & Middleton, 2009;Stafford & Grady, 2003;Verdeli et al, 2011) and a vast civilian literature (Glasheen, Richardson & Fabio, 2010;Nomura, Wickramaratne, Warner, Mufson, & Weissman, 2002;Tunnard, 2004;Weissman & Olfson, 2009). The civilian literature also notes that fathers' and grandparents' mental health may affect children's wellbeing (Pettit, Olino, Roberts, Seeley, & Lewinsohn, 2008;Weitzman, Rosenthal, & Liu, 2011;Wilson & Durbin, 2010).…”
Section: Previous Research On Children and Adolescents In Military Fasupporting
confidence: 71%
See 1 more Smart Citation
“…Inconsolable crying, bed-wetting, aggression and temper tantrums were observed. This early finding that the non-deployed parent's mental health predicted children's depression, internalising and externalising symptoms, mirrors consistent findings in contemporary military family research (Drummet, Coleman, & Cable, 2003;Flake, Davis, Johnson, & Middleton, 2009;Stafford & Grady, 2003;Verdeli et al, 2011) and a vast civilian literature (Glasheen, Richardson & Fabio, 2010;Nomura, Wickramaratne, Warner, Mufson, & Weissman, 2002;Tunnard, 2004;Weissman & Olfson, 2009). The civilian literature also notes that fathers' and grandparents' mental health may affect children's wellbeing (Pettit, Olino, Roberts, Seeley, & Lewinsohn, 2008;Weitzman, Rosenthal, & Liu, 2011;Wilson & Durbin, 2010).…”
Section: Previous Research On Children and Adolescents In Military Fasupporting
confidence: 71%
“…McFarlane (2009) noted a conspicuous lack of research in this area from countries other than the USA. Prior to the recent and ongoing deployments to Iraq and Afghanistan (2001-present), Verdeli et al (2011) concluded that studies throughout the 1980s and 1990s indicated that children and spouses experienced symptoms of depression and anxiety during, and immediately after, the deployment. It was suggested that they managed these demands successfully.…”
Section: Previous Research On Children and Adolescents In Military Famentioning
confidence: 97%
“…In a longitudinal study of couple adjustment and PTSD symptoms in OIF National Guard veterans, Erbes and colleagues found (2011) dysphoria (reflecting generalized distress including aspects of emotional numbing and arousal) had the strongest independent contribution to predicting relationship adjustment at Time 1 and indirectly predicted poorer relationship adjustment at Time 2. However, an exploratory analysis of gender differences found a tendency for avoidance to be more highly related to relationship adjustment among female soldiers at Time 1, Verdeli et al, (2011) focus on the need to treat depression in military spouses and the potential implications of at-home caregiver depression for military children. These authors also discuss the barriers to care for military spouses and finally they present a rationale for adapting mental health interventions to military spouses' unique situation and needs.…”
mentioning
confidence: 96%
“…Notably, a high proportion (41 percent) of NG/R members reported that their spouse/partner experienced mental health problems, such as depression or anxiety, a rate twice that reported by veterans. Previous studies have found high rates of mental health problems and mental health care utilization among military spouses (Larson et al, 2012;Verdeli et al, 2011;Mansfield et al, 2010). Given that many existing mental health resources focus on service members and veterans rather than spouses/ partners, this finding suggests that additional resources are warranted to address the mental health needs of service members' and veterans' families.…”
Section: Spouse/partner Healthmentioning
confidence: 72%